Platypuses - Borgert-Spaniol, Megan, 1989- (Minneapolis, MN : Bellwether Media, Inc., 2016)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces platypuses to young readers through leveled text and related photos"--
What are platypuses? -- Bottom feeders -- Eggs to babies.
Includes bibliographical references and index.
Ages 5-8
K to grade 3
Keywords: Platypus -- Juvenile literature